A study of Relationship between Religious Tourism and Individual’s satisfaction - ASTHANA, DR PRADEEP; PANDEY, POOJA (Revista de turism - studii și cercetări în turism, 2019)
Pilgrimage and religious tourism have become an integrated part of tourism industry. This is linked with the economic development and finding out new destinations. Tourism is deemed as an economic and social activity which benefits the local places and country by generating employment and income, improvement in tourism and allied sector infrastructure etc. Religion has long been an important motive for travel and pilgrimage journeys are often considered as the first form of organized tourism. Religious Tourism can be defined as travel with the core motive of experiencing religious forms, or the products they induce, like art, culture, traditions and architecture. So, modern religious tourism has also become a key driver of socio- economic development of a country.